The political web media, participation and alternative democracy - Dahlgren, Peter 1946- (Palgrave Macmillan, 2013)
"As democracy encounters increasing difficulties, many citizens are turning to the domain of alternative politics, and in so doing, making considerable use of the Web and other new communication technologies. Clearly this is having significant impact, and we see that new modes of political participation and even political cultures are emerging. Yet, we would be foolish to expect some simple 'techno-fix' for democracy; its problems are more complex than that. This volume analyses various factors that shape such Web-facilitated participation, including features of the Web itself as well as broader societal realities. Avoiding simplistic optimism or pessimism, the discussion highlights the tensions and force-fields that impact on participation. The presentation also addresses several key topics in regard to citizens' engagement, such as civic subjectivity, web intellectuals, and cosmopolitanism. While anchored in an extensive literature and wide theoretical vistas, the book is written in a clear and accessible style"--
Includes bibliographical references (pages 178-192) and index
Introduction -- Part I. Politics and Participation on the Web: 1. Democracy, participation and media connections; 2. Force-fields of the web environment -- Part II. Evolving Forms and Practices: 3. The Occupy Wall Street: discursive strategies and fields; 4. Online public intellectuals; 5. Web journalism and civic cosmopolitanism: professional vs. participatory ideals -- Part III. Critical Approaches: 6. The civic and subject and media-based agency; 7. Critical media research: something old, new, and unfinished
Keywords: Internet / Political aspects; Online social networks / Political aspects; Political participation; Mass media / Political aspects; Digital media / Political aspects; Massenmedien; Politik; Demokratie; Internet; Social Media; Politische Beteiligung